PENGEMBANGAN MODUL KIMIA TOPIK SIFAT LARUTAN ASAM BASA KELAS XI IPA DALAM MENINGKATKAN KEMAMPUAN BELAJAR MANDIRI SISWA DI SMA NEGERI 1 TEMINABUAN KABUPATEN SORONG SELATAN - Duwiri, Yuanita Inggrit; Siregar, Tiurlina (Magister Pendidikan IPA, UNCEN, 2016)
The use of modules in the process of learning can improve student learning outcomes, because through the use of the module, students are able to learn independently and do not always depent on the teacher and other parties. This study is a research and development ( R & D) which aims to develop learning modules exiunine the effectiveness of chemistry and the use of modules in the learning press. The design used is one type of equivalent pretest -postest design. The study sample was 46 students were devided into two group : the experimental group of 23 students who use the learning modules and 23 students as a control group without using the module studi.Result showed that there were significant differences between the learning outcomes of students who learn to use the module with students learn without the use of modules. It can be seen the result of the analisys of diferent test N- over all gain, the value obtained is 0,000 significance smaller than 0,05 (p < 0,05). Therefore, the value of N- gain over all in the experimental class that is 0,72 higher than the control clas is 0,68 ( 0,72> 0,68), it can be concluded that the terning module using chemistrycan inprove understanding concepts students learn in order to obtain optimal result. Keywords: Development, Modules, stand alone to study , Liquit caracteristic acid and basa.